Clinical experience with orphan drugs for rare metabolic diseases - Alicia Caso-González; Jesica Núñez-Rodríguez; María-José; Yared González-Pérez; Raquel Marín-Gorricho; Claudia Leralta-González; Carmen Obaldia-Alaña (Elsevier, 2022)
Introduction: Inborn errors of metabolism are a highly heterogeneous group of orphan diseases. Diet therapy and enzyme and coenzyme replacement are the most frequently used treatment. There are few patients and published studies about inborn errors of metabolism. The main objective of this study was to describe the effectiveness of orphan drugs in inborn errors of metabolism in paediatric patients. Material and methods: Retrospective descriptive study of 24 months on patients diagnosed with inborn errors of metabolism during childhood and who attended the pharmacy clinic or Day-Care Unit of a 630-bed general hospital. Results: The study included 15 patients with a median age of 17.8 years and were treated with nine different drugs: sapropterin, sodium phenylbutyrate, miglustat, velaglucerase, sebelipase, idursulfase, 5-hydroxytryptophan, succinate, and riboflavin. Seven different inborn errors of metabolism were observed: phenylketonuria, defects of the urea cycle, Gaucher, Nieman-Pick, Hunter's disease, along with acid lipase deficiency, and mitochondrial diseases. Orphan drugs used for the treatment of inborn errors of metabolism accounted for 1.3% of hospital drug costs. Some orphan drugs achieved asymptomatic patients, but others just produced a modest symptomatic improvement. Most patients showed good tolerance to the treatment. Conclusions: Orphan drugs used in inborn errors of metabolism had an easy to manage toxicity profile, with many disparities in effectiveness. These drugs have a high economic impact. The cost-effectiveness ratio for orphan drugs is a controversial issue due to their high cost and the inconclusive clinical evidence. Resumen: Introducción: Los errores congénitos del metabolismo son un grupo muy heterogéneo de enfermedades raras. La mayoría se pueden tratar con dieta y sustitución enzimática.Existen pocos pacientes y pocos estudios publicados en estas enfermedades. Por ello, se ha llevado a cabo un estudio con el objetivo de evaluar la efectividad de los medicamentos huérfanos utilizados en errores congénitos del metabolismo de un hospital general de 630 camas. Material y métodos: Estudio descriptivo restrospectivo de 24 meses de duración en un hospital general de 630 camas. Se incluyeron los pacientes diagnosticados durante la infancia de errores congénitos del metabolismo y que acudieron a Hospital de Día o a la consulta de Farmacia. Resultados: Se estudiaron 15 pacientes, con una edad media de 17,8 años, que recibieron tratamiento con 9 fármacos: sapropterina, fenilbutirato de sodio, miglustat, velaglucerasa, sebelipasa, idursulfasa, hidroxitriptófano, succinato y riboflavina. Presentaban 7 errores congénitos del metabolismo diferentes: fenilcetonuria, trastorno del ciclo de la urea, Gaucher, Niemann-Pick, Hunter, déficit de lipasa ácida liposomal y defectos mitocondriales. Los medicamentos huérfanos para estos trastornos supusieron el 1,3% del gasto de farmacia. Algunos medicamentos huérfanos lograron que los pacientes estuvieran asintomáticos y otros, sólo produjeron una discreta mejoría. La efectividad de las fórmulas magistrales se evaluó mediante criterios subjetivos. En general, los pacientes presentaron buena tolerancia a estos tratamientos. Conclusiones: Los medicamentos huérfanos utilizados para errores congénitos del metabolismo presentan buen perfil de seguridad pero gran disparidad en cuanto a su efectividad. Suponen un alto impacto económico.La incertidumbre en cuanto a la evidencia clínica de los medicamentos huérfanos junto con el elevado coste, hace que la relación coste-efectividad sea controvertida.